Music and Globalization : Critical Encounters - White, Bob W., 1965- (Book collections on Project MUSE., 2012)
"World music" emerged as a commercial and musical category in the 1980s, but in some sense music has always been global. Through the metaphor of encounters, Music and Globalization explores the dynamics that enable or hinder cross-cultural communication through music. In the stories told by the contributors, we meet well-known players such as David Byrne, Peter Gabriel, Sting, Ry Cooder, Fela Kuti, and Gilberto Gil, but also lesser-known characters such as the Senegalese Afro-Cuban singer Laba Sosseh and Raramuri fiddle players from northwest Mexico. This collection demonstrates that careful historical and ethnographic analysis of global music can show us how globalization operates and what, if anything, we as consumers have to do with it.